PENGARUH HUMAN CAPITAL MANAGEMENT TERHADAP KUALITAS PELAYANAN YANG DIMEDIASI OLEH PENGEMBANGAN KARIR PADA KARYAWAN VILLA, DESA KALISADA, BULELENG-BALI - Sudarnaya, I Ketut; Martini, Komang Rina (Jurnal Daya Saing, 2023)
The purpose of this study was to find out how human capital management influences service quality with career development as a mediating variable. This study uses a quantitative approach. The data collection technique used in this study was a questionnaire and documentation technique. The total population and sample used were 40 people from 5 (five) villas in Kalisada Village, Buleleng-Bali which consisted of Manik Segara Villa, Mahkai Villa, Medium Villa, Palmeira Villa and Le Petit Leon Villa. The data analysis technique used in this study is SEM-PLS (Structural Equation Modeling- Partial Least Square) mode using SMARTPLS3 to process research data. The relationship examined in this study showed one result that was not significant and the other results had a positive and significant effect. Therefore, villa companies are expected to be able to improve employee careers by looking at how large the human capital management is and the quality of service each employee has. Keywords: Human Capital Management, Service Quality and Career development